2021
DOI: 10.1155/2021/6635814
|View full text |Cite
|
Sign up to set email alerts
|

Aged Persons Living with HIV and Nutritional Wellness: Analysis of 2013 South Africa-SAGE Well-Being of Older People Study (WOPS) Wave 2

Abstract: Introduction. This study sought to examine the nutritional wellness among aged persons living with HIV in Somkhele, South Africa. Methods. Data were extracted from the 2013 South Africa-SAGE Well-Being of Older People Study (WOPS) Wave 2. The study sampled 440 aged persons (50 years and above). The proportion of the aged persons with high nutritional wellness by key covariates was reported with chi-square and p -values ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…In this study, older people are categorised as younger old (50–64), young old (65–74 years), old old (75–84 years), and the oldest old (85 years and above) [ 20 ]. Data utilised in this study were acquired from the WHO SAGE Well-Being of Older People Study (WOPS).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, older people are categorised as younger old (50–64), young old (65–74 years), old old (75–84 years), and the oldest old (85 years and above) [ 20 ]. Data utilised in this study were acquired from the WHO SAGE Well-Being of Older People Study (WOPS).…”
Section: Methodsmentioning
confidence: 99%
“…These were population-based HIV surveys conducted in South Africa between 2010 (Wave 1) and 2013 (Wave 2) in collaboration with the Africa Centre Demographic Information System (ACDIS) [ 21 ]. The SAGE WOPS study gathers comparable longitudinal data on a variety of health, demographic, and social markers that are relevant to the health and functional status of older persons who are HIV-positive or have HIV/AIDS in their family [ 20 ]. In addition, the survey looked at the respondents’ nutritional status, and HIV treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Masa et al ( 2018 ) concluded that the diets of older PLWH were mostly carbohydrates and this was based on socio-economic factors and the staple food available. In South Africa, Oduro and Kissah-Korsah ( 2021 ) describe a more diverse diet among older PLWH and conclude that 38.9% of older PLWH had at least three servings of fruit and vegetables with most considering their diet as good.…”
Section: Introductionmentioning
confidence: 99%